Welding metallic materials - Scutt, Don; Double D Technical Productions (Wellington : Double D Technical Productions, 2001)
Part A of this CD-ROM covers topics of production of stick electrodes ; manual metal arc welding ; submerged arc welding ; gas tungsten arc welding (TIG) ; keyhole gas tungten arc welding ; resistence welding-projection & spot ; laser beam welding ; electron beam welding - Part B covers gas metal arc welding (MIG) ; determination of pre-heat ; narrow gap welding ; flux cored arc welding ; plasma transferred arc welding ; friction stir welding ; oxy-acetlyene welding and thermit welding.
narrator: Terry Trewavas
Keywords: Electric welding; Electron beam welding; Welding